Trinitarian Hagiography in Late Medieval England: Rewriting St Robert of Knaresborough in Latin Verse - Blair, Hazel J. Hunter (Studies in church history, 2021)
The Order of the Holy Trinity for the Redemption of Captives (or Trinitarian Order) is one of the least studied continental religious groups to have expanded into thirteenth-century England. This article examines shifting notions of Trinitarian redemption in late medieval England through the prism of the order's writing about Yorkshire hermit St Robert of Knaresborough (d. 1218). Against the Weberian theory of the routinization of charisma, it demonstrates that Robert's inspirational sanctity was never bound too rigidly by his Trinitarian hagiographers, who rather co-opted his unstable charisma in distinct yet complementary ways to facilitate institutional reinvention and spiritual flourishing in the fourteenth and fifteenth centuries.